A statistical determination of the transit speed of pollutants in a water reservoir affected by acid mine drainage from the iberian pyrite belt - de la Torre, M. L. (2017)
The El Sancho reservoir is located in the Odiel River basin, which crosses the Iberian Pyrite Belt. The reservoir receives acid mine drainage (AMD) from the Meca River, a tributary of the Odiel River. Two multi-parameter probes, one placed at the tail (up-gradient) end of the reservoir, where the contaminants enter, and another close to the reservoir dam were used to characterize acidity migration through the Sancho reservoir. The probes both measured pH and conductivity every 30 min. Two different levels of contamination were found, due to dilution that takes place within the reservoir and changes in the AMD composition. The cross-correlation function allowed quantification of the migration process from tail to dam. For both pH and conductivity, the maximum correlation occurred 17 days after sampling, indicating a mean transit time of 17 days. Since the distance between the two sampling points was 14,500 m, the contaminant transit speed was 0.0098 m/s.